The Economy of Colonial Malaya: Administrators versus Capitalists by Sivachandralingam Sundara Raja - Viswanathan Selvaratnam (Kajian Malaysia, 2022)
Sivachandralingam Sundara Raja’s study The Economy of Colonial Malaya: Administrators versus Capitalists was published in 2018 by Routledge, under their “Modern History in Asia Series”. The publication is adapted from a doctoral dissertation that the author pursued in the Department of History, Universiti Malaya. Embedded within a Eurocentric methodological framework, the main objective of the study was to rectify and bridge the gaps in Malaysia’s late 19th and early 20th-century colonial-era historiography, in order to better understand the nation’s imperial economic history.